Empty words: Buddhist philosophy and cross-cultural interpretation - Garfield, Jay L. (Oxford University Press, 2002)
This volume collects Jay Garfield's essays on Madhyamaka, Yogacara, Buddhist ethics and cross-cultural hermeneutics. The first part addresses Madhyamaka, supplementing Garfield's translation of Fundamental Wisdom of the Middle Way (OUP, 1995), a foundational philosophical text by the Buddhist saint Nagarjuna. Garfield then considers the work of philosophical rivals, and sheds important light on the relation of Nagarjuna's views to other Buddhist and non-Buddhist philosophical positions